Five Points Towards an Architecture In-Formation - Stavros Kousoulas; Dulmini Perera (Footprint)
While there have been significant discussions about the relevance of cybernetics within architectural and urban studies, the focus has mainly been on computing and digital practices. Since its emergence in the post-war period, cybernetics – in both its first and second-order versions – has introduced to architectural discourse systematic design methods and practices, while also tackling issues of reflexivity and complex problems. In this introduction, we examine the relation between cybernetics and architecture by focusing on a problem they both share. To this end, we approach cybernetics as the study of the production, consumption and flow of information, an account that has little to do with digital logics, unless one wants to pursue that special case. Therefore, cyberneticisation can set the foundations for a relational account that examines how signs are communicated and how meaning is produced and experienced within systems. This third-order cybernetics extends beyond the original scope of living organisms and their environments in order to include ecologies of ideas, power, institutions, media and so on. In this sense, cyberneticisation is radically environmental, positing the primacy of relations over fixed terms, binary oppositions and linear logics, making it high time for architectural and urban studies to take into consideration its ground-breaking potentials. By introducing five short points on the relation between architecture and cybernetics, we aim to assist in this endeavour.